Shared work? Unravelling interspecies entanglements, agency, and the rhythms of equids at work - Watson, Tamlin; Clancy, Cara (Frontiers in Veterinary Science, 2025)
Focusing on donkeys, this paper examines the type and scope of ‘work’ undertaken by working equids in three very different contexts in the United Kingdom, Europe and the Global South (case studies). Drawing on the concepts of ‘animal work’ and ‘nonhuman labour’ as discussed by critical theorists such as Porcher, Estebanez, Coulter, Barua and others we aim to: (i) Elaborate on the concept of ‘shared work’ by bringing key animal welfare concepts into dialogue with emerging literature on animal labour through a relational theoretical lens; (ii) Explore the nature of equid work including its physicality, and also the freedoms and opportunities that are afforded to equids (in terms of rest, play and kinship); (iii) Illustrate how work may be experienced by the equids themselves, using vignettes based on ‘more-than-human’ ethnographic fieldwork so as to foreground the equid perspective and illuminate questions of agency, sentience and subjectivity.